Comparison of three different LCIA methods EDIP97, CML2001 and Eco-indicator 99. - Dreyer, Louise Camilla (The International Journal of Life Cycle Assessment)
Goal, Scope and Background. A number of impact assessment methodologies are available to the LCA practitioner. They differ, and often there is not one obvious choice among them. The question therefore naturally arises : Does it make any difference to my conclusions which method I choose? To investigate this issue, a comparison is performed of three frequently applied life cycle impact assessment methods. Methods. The three life cycle impact assessment methods EDIP97 [1], CML2001 [2] and Eco-Indicator 99 [3] are compared on their performance through application to the same life cycle inventory from a study of a water based UV lacquer. EDIP97 and CML2001 are both midpoint approaches and hence quite similar in their scope and structure, and this allows a comparison during both characterisation and normalisation. The third impact assessment method Eco-indicator 99 is an endpoint method and different in scope and structure from the other two. A detailed comparison can not be done but a comparative analysis of the main contributors to the Eco-indicator 99 results and the weighted and aggregated EDIP97 results is performed. Results and Discussion. Following a translation into common units of the EDIP97 and CML2001 output, differences up to two orders of magnitude are found for some of the indicator results for the impact categories describing toxicity to humans and ecosystems, and there is little similarity in the patterns of major contributors among the two methods. For human toxicity the CML2001 score is dominated by contribution frommetals while the EDIP97 score is caused by a solvent and nitrogen oxides. For aquatic ecotoxicity, metals are the main contributors for both methods but while it is vanadium for CML2001, it is strontium for EDIP97. After normalisation, the differences are reduced but still considerable. For the other impact categories, the two methods show only minor differences. The comparison of the main contributors to the Eco-indicator 99 results and the weighted and aggregated EDIP97 results identifies nitrogen oxides as the main contributor for both methods. It is, however, much more dominant for Eco-indicator 99 while the EDIP97 score represents important contributions from a number of different substances, and furthermore, the analysis reveals that the aggregated scores for the two methods come from different impacts. It is thus difficult to extend the findings for these two methods to other inventories. Conclusion. For EDIP97 and CML2001, it mainly matters which method is used if the chemical impacts on human health and ecosystem health are important for the study. For the other impact categories, the differences are minor for these two methodologies. For EDIP97 and Eco-Indicator 99, the patterns of most important contributors to the weighted and aggregated impact scores are rather different, and considering the known differences in the underlying framework and models, the results of the two methods may well go in opposite directions for some inventories even if the conclusion is the same for the inventory studied in this paper. Recommendations and Outlook. Particularly for the impact categories representing toxic impacts from chemicals, the study demonstrates the need for more a detailed analysis of the causes underlying the big differences revealed between the methods.